ENGLISH TEACHING MATERIALS FOR KINDERGARTENS - , SAKINAH ADELIA FIIMANTI, Nur Endah Nugraheni, S.S., M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Early Childhood Education is the main basic of education for the people. It happens in the golden ages, 3 to 7 years old. Recently, there are many parents who support their children in golden ages to get the school which has Early Childhood Education or pre kindergarten program. It uses method of learning by playing which is fun for children. English lesson is already included in the basic curriculum for Early Childhood Education. Pre-school/ pre-kindergarten students begin to study English lesson which is easy and proper for their ages. However, the materials must be adapted to both the theory of Early Childhood Education and the cognitive capability of the children. Yet, it has not already implemented by kindergartens in Yogyakarta comprehensively. By this graduating paper, the writer wants to explain about the theory of Early Childhood Education and the proper English materials for the children in Kindergarten. The writer uses the mostly data from the library research method. Also few data is taken from some Kindergartens in Yogyakarta by interviewing the teachers. The writer also uses content analysis method to explore the contents the book. The results of this graduating paper conclude that the English materials for Kindergarten students are proper to the curriculum of Early Childhood Education, the cognitive capability of the student and also the studentâs need.